PENDIDIKAN ISLAM DAN IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS (SDGs) - sianly, Sekar; Dinanti Rusti, Dinda; Heriyati , Fika; Veriska; Zaman, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the relationship between United Nations Sustainable Development Goals (SDGs) and Islamic education in supporting sustainable development. The background of this research is based on global challenges such as poverty, environmental damage, social inequality, and the low quality of education, which require educational solutions rooted in moral and social values. This study aims to analyze the role of Islamic education in supporting the implementation of SDGs and the integration of sustainable development values into Islamic educational institutions. The method used in this research is library research by examining various books, scientific journals, articles, and official documents related to Islamic education and SDGs. The results of the study show that Islamic education has values that are in line with the principles of sustainable development, such as justice, social responsibility, environmental awareness, and character building. The implementation of SDGs in Islamic education can be carried out through curriculum development, learning activities, and educational policies that support sustainability values. Therefore, Islamic education has a strategic role in creating a knowledgeable, ethical, and socially responsible generation capable of contributing to sustainable development in the future.